5GASP continuous integration - Direito, Rafael das Neves Simões (2022)
The wide adoption of an NFV-oriented paradigm by network operators proves the importance of NFV in the future of communication networks. This paradigm allows network operators to speed up the development process of their services, decoupling hardware from the functionalities provided by these services. However, since NFV has only been recently globally adopted, several questions and difficulties arose. Network operators need to ensure the reliability and the correct behavior of their Virtualized Network Functions, which poses severe challenges. Thus, the need for developing new validation tools, which are capable of validating network functions that live in an NFV ecosystem. 5GASP is a European project which aims to shorten the idea-to-market process by creating a fully automated and selfservice 5G testbed and providing support tools for Continuous Integration in a secure and trusted environment, addressing the DevOps paradigm. Being aligned with 5GASP’s goals, this dissertation mainly addresses the development of tools to validate NetApps. To accomplish this, this document introduces two different mechanisms for validating NetApps. The first tool is responsible for statically validate the NetApps before they are deployed in 5GASP’s testbeds, being denominated by NetApp Package Validator. Regarding this tool, during this document the focus is its Descriptors Validator Module, which validates the NetApp descriptors through syntactic, semantics, and reference validation and supports NetApps developed according to different Information Models. The second tool comprises an automated validation pipeline. This pipeline validates the functionality and the behavior of the NetApps once they are deployed in a 5G-testbed. Besides, it collects several metrics to enable a better understanding of the NetApp’s behavior. Both tools are expected to be integrated with the 5GASP’s ecosystem. This document presents the requirements definition, architecture, and implementation of these tools and presents their results and outputs.